Alloy material for electromagnetic valve body and preparation method

By adjusting the alloy material composition and manufacturing process of the solenoid valve body, the cracking problem caused by the poor thermoplasticity of ferritic stainless steel was solved, achieving efficient forming and performance improvement of the solenoid valve body.

CN119506704APending Publication Date: 2025-02-25HUAI JI DENG YUE VALVE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411465189.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The poor thermoplasticity of existing ferritic stainless steel materials makes the solenoid valve body prone to cracking during deformation, especially the valve body of solenoid valves with airtight requirements is difficult to manufacture.

Method used

The solenoid valve body is prepared using an alloy material with a specific composition, including C 0.010–0.025%, Si 0.50–1.50%, Mn 0.10–0.30%, P 0.010–0.030%, S 0.010–0.020%, Cr 17.0–19.0%, Ni 0.30–0.80%, Mo 2.0–2.5%, Al 0.10–0.30%, Ti 0.02–0.05%, with the balance being Fe. The solenoid valve body is prepared by hot rolling and peeling, grinding, electrothermal upsetting, forging, and annealing.

Benefits of technology

It improves the thermoplasticity of alloy materials, prevents cracking, increases material utilization, reduces production costs, and enhances performance indicators such as grain size, coercivity, elastic limit, yield point, and tensile strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506704A_ABST
    Figure CN119506704A_ABST
Patent Text Reader

Abstract

The invention discloses an alloy material for an electromagnetic valve body and a preparation method, and the alloy material comprises the following components in percentage by weight: 0.010 to 0.025 percent of C, 0.50 to 1.50 percent of Si, 0.10 to 0.30 percent of Mn, 0.010 to 0.030 percent of P, 0.020 to 0.030 percent of S, 17.0 to 19.0 percent of Cr, 0.30 to 0.80 percent of Ni, 2.0 to 2.5 percent of Mo, 0.10 to 0.30 percent of Al, 0.02 to 0.05 percent of Ti and the balance of Fe. The alloy material is good in thermoplasticity, not prone to cracking in the deformation process and capable of being formed through forging and pressing after electric heating upsetting, the grain size of the material in the hot forming process is improved, and the coercive force, the elastic limit, the yield point, the tensile strength and other parameter indexes of the alloy material are all good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of parts processing, in particular to an alloy material for a solenoid valve body and a preparation method thereof. Background Art

[0002] At present, the solenoid valve body is generally made of ferritic stainless steel bars, which became the industry standard on April 1, 2018. The typical ferritic stainless steel bars are 0Cr18Si2Mo2. The chemical composition of ferritic stainless steel bars of 0Cr18Si2Mo2 by weight percentage is as follows: C content ≤ 0.040%, Si content 1,00-2.00%, Mn content ≤ 0.50%, Cr content 16.5-18.5%, S content ≤ 0.040%, P content ≤ 0.035%, Mo content 1.00-2.00%.

[0003] In the process of preparing the solenoid valve body by hot forging process using the above material, due to the poor thermoplasticity of the material, it has a certain tendency to crack during the deformation process, especially for the solenoid valve body with airtightness requirements, it is more difficult to prepare a qualified solenoid valve body.

[0004] Therefore, there is a need for an alloy material that can improve thermoplasticity so that it can be forged after electric upsetting. The alloy material can improve thermoplasticity and improve grain size during hot forming, thereby reducing the tendency to heat during hot forming. Ultimately, the alloy material can be forged after electric upsetting to produce a blank that meets the required appearance of the product, and then mechanically processed to meet the product size requirements, effectively improving material utilization and reducing production costs. Summary of the invention

[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide an alloy material for a solenoid valve body and a preparation method thereof, which can solve the problems described in the background technology.

[0006] The technical solution to achieve the purpose of the present invention is: an alloy material for a solenoid valve body, comprising, by weight percentage:

[0007] C content is 0.010-0.025%, Si content is 0.50-1.50%, Mn content is 0.10-0.30%, P content is 0.010-0.030%, S content is 0.010-0.020%, Cr content is 17.0-19.0%, Ni content is 0.30-0.80%, Mo content is 2.0-2.5%, Al content is 0.10-0.30%, Ti content is 0.02-0.05%, and the balance is Fe.

[0008] A method for preparing a solenoid valve body based on the alloy material comprises the following steps:

[0009] Step 1: selecting ferritic stainless steel made from the alloy material, hot-rolling and peeling the ferritic stainless steel to obtain a first ferritic stainless steel, and grinding the first ferritic stainless steel to obtain a second ferritic stainless steel;

[0010] Step 2: Cut the second ferritic stainless steel into short bars, and round off both ends of the short bars;

[0011] Step 3: Perform electric heating upsetting on the short rod with rounded corners so that one end of the short rod is in the shape of a garlic head, thereby obtaining a hot upsetting piece;

[0012] Step 4: Place the hot forged piece into the die and forge it into a blank of the solenoid valve body at one time;

[0013] Step 5: anneal the blank at 800-900℃±10℃ for 30-60 minutes, cool it to 600℃±10℃ with the furnace, and air cool it after it is taken out of the furnace;

[0014] Step 6: Test the magnetic properties of the blank. If it is qualified, fine-process it to form the finished solenoid valve body to complete the preparation.

[0015] Further, in step 1, the diameter of the ferritic stainless steel is 12.5 mm.

[0016] Further, in step 1, the diameter of the first ferritic stainless steel is 11.9 mm.

[0017] Further, in step 1, the diameter of the second ferritic stainless steel is 11.7 mm±0.02 mm.

[0018] Beneficial effects of the present invention: The alloy material of the present invention has good thermoplasticity, is not easy to crack during deformation, can be formed by forging after electric upsetting, and improves the grain size of the material during hot forming. The alloy material has good parameters such as coercive force, elastic limit, yield point and tensile strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is the true stress-strain curve of the material at 800℃ and 0.1mm / s (cold-drawn state and annealed state);

[0020] Figure 2 It is a schematic diagram of the force-deformation curve corresponding to Test 3 in Table 2;

[0021] Figure 3 It is the schematic diagram of the hysteresis loop corresponding to Experiment 3 in Table 2;

[0022] Figure 4 It is a schematic diagram of the force-deformation curve corresponding to Test 4 in Table 3;

[0023] Figure 5 This is a schematic diagram of the hysteresis loop corresponding to Experiment 4 in Table 3. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with the accompanying drawings and specific implementation plans:

[0025] like Figure 1-Figure 5 As shown, an alloy material for a solenoid valve body comprises, by weight percentage:

[0026] C content is 0.010-0.025%, Si content is 0.50-1.50%, Mn content is 0.10-0.30%, P content is 0.010-0.030%, S content is 0.020-0.030%, Cr content is 17.0-19.0%, Ni content is 0.30-0.80%, Mo content is 2.0-2.5%, Al content is 0.10-0.30%, Ti content is 0.02-0.05%, and the balance is Fe.

[0027] The above-mentioned element content ranges include both end values. For example, the C content is 0.010-0.025%, that is, the C content is [0.010%, 0.025%], which includes both end values. The same is true for other contents.

[0028] The following three tables are statistical tables of indicators of four tests corresponding to different contents of each component.

[0029]

[0030] Table 1

[0031]

[0032]

[0033] Table 2

[0034] element Test 4 (unsatisfactory indicators) C 0.038 Coercive force Hc(≤450):316.9 Si 1.458 Saturation magnetic induction intensity (≥0.9): 1.353 Mn 0.370 Residual magnetic induction (≤0.5): 0.5851 P 0.022 Yield strength (N / mm2): 591 S 0.011 Tensile strength (N / mm2): 670 Cr 18.900 Elongation after break (%): 21.08 Ni 0.449 End face shrinkage (%): 65.33 Mo 2.250 Al 0.120 Ti 0.008 Residue Fe

[0035] Table 3

[0036] Referring to Tables 1 to 3, Table 1 includes two specific content tests with suboptimal index effects compared to Table 2. Table 2 is the test with the most ideal index among the four tests. In Table 2, the C content is 0.023%, the Si content is 1.485%, the Mn content is 0.2%, the P content is 0.02%, the S content is 0.021%, the Cr content is 17.780%, the Ni content is 0.449%, the Mo content is 2.02%, the Al content is 0.12%, the Ti content is 0.05%, and the rest is Fe. The yield strength and tensile strength obtained in this test are significantly higher than those of the other tests, and the comprehensive performance of each index is good. Table 3 is a test with unsatisfactory indexes.

[0037] refer to Figure 2-Figure 5 , Figure 2 This is a schematic diagram of the force-deformation curve corresponding to Test 3 in Table 2. Figure 3 It is the schematic diagram of the hysteresis loop corresponding to Experiment 3 in Table 2; Figure 4 This is a schematic diagram of the force-deformation curve corresponding to Test 4 in Table 3. Figure 5 This is a schematic diagram of the hysteresis loop corresponding to Experiment 4 in Table 3.

[0038] Among them, C (carbon): carbon content ≥ 0.03%, which means that the formation of carbides will affect the magnetic properties of steel, especially increase the coercivity of alloy materials, and a lower carbon content is conducive to avoiding the formation of excessive carbides. Therefore, the C content of the present invention is limited to between 0.010 and 0.025%.

[0039] Si (silicon): Silicon is used as a reducing agent and deoxidizer in the steelmaking process. If the silicon content exceeds 0.5%, silicon is considered an alloying element, so the Si content of the present invention is 0.50-1.50%. Silicon can significantly improve the elastic limit, yield point and tensile strength of steel. Adding 1.0-1.2% silicon to quenched and tempered structural steel can increase the strength by 15-20%. Low carbon steel containing 1-4% silicon has extremely high magnetic permeability. If the silicon content is higher than 1%, the plasticity and impact toughness of the steel will be reduced. If the silicon content exceeds 2.2%, the welding performance of the steel will be reduced. It has a decisive influence on its organization, texture and magnetic properties. As the silicon content increases, the resistivity increases, the γ phase region shrinks, the eddy current loss decreases, the grains coarsen, the hysteresis loss decreases, the iron loss value decreases and the magnetic induction value also decreases. Silicon can reduce the harm of impurity elements in steel, graphitize carbon, and reduce the harmful effect of carbon on magnetic properties; silicon has an affinity with oxygen, plays a deoxidizing role, and forms silicon nitride with nitrogen to reduce the solubility of nitrogen in steel. In short, the silicon content cannot be too high or too low, and the elastic limit, yield point and tensile strength need to be considered to determine the silicon content.

[0040] Manganese (Mn): In the steelmaking process, manganese is a good deoxidizer and desulfurizer. Generally, steel contains 0.30-0.50% manganese. It can improve the strength, hardness and wear resistance of steel. In addition, trace amounts of manganese can reduce the critical cooling rate of steel, improve the toughness of steel, and improve the hot working properties of steel.

[0041] Phosphorus (P): In general, phosphorus is a harmful element in steel, which will increase the cold brittleness of steel, deteriorate welding performance, reduce plasticity, and deteriorate cold bending performance. Therefore, the phosphorus content in steel is usually required to be less than 0.035%, and the requirement for high-quality steel is even lower.

[0042] Sulfur (S): Sulfur is also a harmful element under normal circumstances. Sulfur will reduce the mechanical properties of steel, increase the tendency of steel to crack, make steel hot brittle, reduce the ductility and toughness of steel, and cause cracks during forging and rolling. Sulfur is also detrimental to welding performance and reduces corrosion resistance. Therefore, the sulfur content is usually required to be less than 0.035%. In mechanical manufacturing, in order to improve the cutting performance of steel and make it easy to cut, increasing the sulfur content to 0.1-0.4% can form sulfides, which interrupt the continuity of the matrix and improve the cutting performance of the material. When the sulfur content is lower than 0.01%, it will make it difficult to cut. Therefore, increasing the sulfur content and controlling it between 0.02 and 0.03 will improve the cutting performance to a certain extent, and will not affect the welding performance and corrosion resistance of the solenoid valve.

[0043] Chromium (Cr): In structural steel and tool steel, chromium can significantly improve strength, hardness and wear resistance, but at the same time reduce plasticity and toughness. Chromium can also improve the heat resistance, oxidation resistance and corrosion resistance of steel. When the chromium content is higher than 8%, the steel can be resistant to corrosion media such as strong oxidizing acids. It is an important alloying element for stainless steel.

[0044] Molybdenum (Mo): Molybdenum can improve the alloy's resistance to pitting corrosion, significantly enhance the stability of the passivation film, and also have a certain effect on the alloy's comprehensive magnetic properties.

[0045] Nickel (Ni): Nickel can increase the strength of steel without reducing its plasticity and improve the toughness of steel. It has a certain corrosion resistance and has good corrosion resistance to some reducing acids.

[0046] Aluminum (Al): Aluminum can play a good deoxidation role in steelmaking, refine the grains of steel, and improve the strength of steel. For the hot upsetting solenoid valve body of the present invention, it can effectively prevent the excessive growth of the grain size of the material during the hot upsetting and annealing process.

[0047] Titanium (Ti): Titanium has a strong affinity with nitrogen, oxygen, and carbon, and has a stronger affinity with sulfur than iron. Therefore, it is a good deoxidizing and degassing agent and an effective element for fixing nitrogen and carbon. However, excessive Ti will form TiS (titanium sulfide) particles, which will affect the air tightness of the solenoid valve body, so the titanium content needs to be controlled. The inventors found that the titanium content is most suitable when it does not exceed 0.05.

[0048] The invention adjusts the chemical composition of the alloy material for the electromagnetic valve, improves the magnetic property and mechanical property of the alloy material, and makes the alloy material more suitable for processing and manufacturing the electromagnetic valve by using the hot upsetting forging process.

[0049] The solenoid valve body made of the alloy material composed of the above materials has a grain size of 5.0-5.5 at the edge position of the solenoid valve body - metallographic magnification 100x, and a grain size of 6.5-7.0 at the center position - metallographic magnification 100x.

[0050] The present invention also provides a method for preparing a solenoid valve body based on the alloy material, comprising the following steps:

[0051] Step 1: Select ferritic stainless steel made of the alloy material, the diameter of the ferritic stainless steel is 12.5 mm (millimeter), perform hot rolling and peeling treatment on the ferritic stainless steel to obtain a first ferritic stainless steel with a diameter of 11.9 mm, and then perform grinding treatment on the first ferritic stainless steel to obtain a second ferritic stainless steel with a diameter of 11.7 mm±0.02 mm.

[0052] Step 2: Cut the second ferritic stainless steel into short bars, and round both ends of the short bars.

[0053] Step 3: The short rod with rounded corners is subjected to electric upsetting so that one end of the short rod is in the shape of a garlic head, thereby obtaining a hot upsetting part.

[0054] Step 4: Place the hot forged piece into the die and forge it into a blank of the solenoid valve body in one step.

[0055] Step 5: Anneal the blank at 800-900℃±10℃ for 30-60 minutes, cool it to 600℃±10℃, and air cool it out of the furnace. The grain size of the blank reaches 4-7 levels, so that the magnetic properties of the blank reach the standard state and meet the requirements of the minimum working voltage and temperature rise.

[0056] Step 6: Test the magnetic properties of the blank. If it is qualified, fine-process it to form the finished solenoid valve body to complete the preparation.

[0057] The alloy material of the present invention has good thermoplasticity, is not easy to crack during deformation, can be formed by forging after electric upsetting, and improves the grain size of the material during hot forming. The alloy material has good parameters such as coercive force, elastic limit, yield point and tensile strength.

[0058] The embodiment disclosed in this specification is only an example of a unilateral feature of the present invention, and the protection scope of the present invention is not limited to this embodiment, and any other functionally equivalent embodiments fall within the protection scope of the present invention. For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.

Claims

1. An alloy material for a solenoid valve body, characterized in that: By weight percentage, including: C content is 0.010-0.025%, Si content is 0.50-1.50%, Mn content is 0.10-0.30%, P content is 0.010-0.030%, S content is 0.020-0.030%, Cr content is 17.0-19.0%, Ni content is 0.30-0.80%, Mo content is 2.0-2.5%, Al content is 0.10-0.30%, Ti content is 0.02-0.05%, and the balance is Fe.

2. A method for preparing a solenoid valve body based on the alloy material according to claim 1, characterized in that: The following steps are involved: Step 1: selecting ferritic stainless steel made from the alloy material according to claim 1, hot-rolling and peeling the ferritic stainless steel to obtain a first ferritic stainless steel, and grinding the first ferritic stainless steel to obtain a second ferritic stainless steel; Step 2: Cut the second ferritic stainless steel into short bars, and round off both ends of the short bars; Step 3: Perform electric heating upsetting on the short rod with rounded corners so that one end of the short rod is in the shape of a garlic head, thereby obtaining a hot upsetting piece; Step 4: Place the hot forged piece into the die and forge it into a blank of the solenoid valve body at one time; Step 5: anneal the blank at 800-900℃±10℃ for 30-60 minutes, cool it to 600℃±10℃ with the furnace, and air cool it after it is taken out of the furnace; Step 6: Test the magnetic properties of the blank. If it is qualified, fine-process it to form the finished solenoid valve body to complete the preparation.

3. The method for preparing a solenoid valve body based on the alloy material according to claim 1, characterized in that: In step 1, the diameter of the ferritic stainless steel is 12.5 mm. 4 . The method for preparing a solenoid valve body based on the alloy material according to claim 1 , wherein in step 1 , the diameter of the first ferritic stainless steel is 11.9 mm. 5 . The method for preparing a solenoid valve body based on the alloy material according to claim 1 , wherein in step 1 , the diameter of the second ferritic stainless steel is 11.7 mm±0.02 mm.